2021
DOI: 10.5603/fm.a2020.0049
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical landmarks effective in the localisation of the median nerve during orthopaedic procedures

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…In a study with 10 cadaveric specimens, McCann et al (2012) identified the main trunk of the median nerve to be on average 0.89 cm (SD = ± 0.56 cm) ulnar to the flexor carpi radialis (FCR) tendon measured from the center of the two structures at the level of the watershed line of the distal radius. Mizia et al (2021) confirmed a similar distance (0.79 cm CI = 0.74-0.84) from the main trunk of the median nerve to the FCR tendon measured at the level of the proximal flexor retinaculum.…”
Section: Median Nervesupporting
confidence: 78%
See 1 more Smart Citation
“…In a study with 10 cadaveric specimens, McCann et al (2012) identified the main trunk of the median nerve to be on average 0.89 cm (SD = ± 0.56 cm) ulnar to the flexor carpi radialis (FCR) tendon measured from the center of the two structures at the level of the watershed line of the distal radius. Mizia et al (2021) confirmed a similar distance (0.79 cm CI = 0.74-0.84) from the main trunk of the median nerve to the FCR tendon measured at the level of the proximal flexor retinaculum.…”
Section: Median Nervesupporting
confidence: 78%
“…The palmar cutaneous branch of the median nerve (PCBMN) was located on average 0.34 cm (SD = 0.27 cm) from the FCR tendon measured from the center of the two structures at the level of the watershed line of the distal radius (McCann et al, 2012). Using ultrasound in 114 upper limbs of healthy volunteers, the median nerve was located at an average distance of 0.79 cm (95% CI: 0.74–0.84) ulnar to the FCR at the level of the proximal flexor retinaculum (Mizia et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Incisions induced painful scars that may also present after surgical release [19]. For surgical incision making, one group reported an anatomical safe space to avoid iatrogenic injury by palpating and measuring the distance between the flexor carpi radialis and flexor carpi ulnaris tendon [20]. Our entry and exit points described before are all located in this safe area.…”
Section: Plos Onementioning
confidence: 83%
“…Some researchers suggest that the FCU is an important anatomical landmark for surgeons and ultrasonographers. Knowledge of the variability of the terminal segment of this muscle is therefore not only of cognitive importance but also of profound clinical significance (Mizia et al 2021).…”
Section: Discussionmentioning
confidence: 99%